Marwan Sahmarani: Marie Marie, the devil in me has taken you for a ride - Sahmarani, Marwan (Dubai; Lawrie Shabibi, 2012)
Exhibition catalog. Dec 2011- Feb 2012. Text: Laura Egerton.
English
Keywords: N4390-5098 Visual Arts- Exhibitions